Exploring the Complementarities Within High‐Performance Work Systems: A Set‐Theoretic Analysis of UK Firms. Issue 4 (21st June 2016) - Meuer, Johannes
Abstract : High‐performance work systems (HPWS) are important conceptual instruments in the human resource management literature. Yet our current understanding of the complementarities within HPWS remains limited for two reasons: First, the dominant theoretical perspectives on HPWS provide a landscape of theoretical possibilities rather than an understanding of different possibilities through which HPWS generate positive effects on performance; and second, the literature on HPWS merely proposes several seemingly equally important HR practices. This article explores the internal nature of HPWS by integrating a configurational perspective of core, peripheral, and nonessential HR practices with a typology of complementarities. Analyzing 530 UK‐based firms using fuzzy set qualitative comparative analysis (fsQCA), I identify four frequently implemented HPWS consistently associated with high labor productivity. The complementarities within all HPWS combine pairs of core HR practices with sets of peripheral HR practices. Moreover, the complementarities within three of the four HPWS rely on firms' avoidance of implementing certain HR practices. The results suggest that the synergies of HPWS arise from efficient complementarities and virtuous overlaps, and reveal the significance of achieving high performance by not implementing HR practices. This article thus advances a new perspective on HPWSs, highlighting the challenges involved in successfully designing HPWS. © 2016 Wiley Periodicals, Inc.